Reforming Contempt of Court Regulation in Indonesia: Addressing Indirect Interference and Trial by the Press - Neisa Angrum Adisti; Febrian; Febby Mutiara Nelson (Sriwijaya Law Review, 2026)
Contempt of court refers to acts threatening the dignity, independence, and integrity of the judicial process. In Indonesia, the regulatory treatment of contempt of court remains fragmented and incomplete. Existing provisions, including those in the Criminal Code, primarily focus on direct disruptions during court proceedings, while failing to address broader, subtler forms of interference adequately. This regulatory gap contributes to legal uncertainty and inconsistent enforcement. A notable omission is the lack of clear mechanisms to regulate indirect contempt, such as trial by the press, in which excessive or prejudicial media coverage can influence public opinion, undermine the presumption of innocence, and jeopardise judicial impartiality. This research examines the urgent need for a dedicated and comprehensive legal framework governing contempt of court in Indonesia, addressing the philosophical foundations, the urgency of enacting a specific and impartial regulation, and the limited scope of indirect forms of trial by the press under Indonesia's national Criminal Code. Employing normative legal research, this study draws upon statutory analysis, conceptual exploration, and comparative legal approaches. As a result, a comprehensive contempt of court statute is urgently needed not merely to shield judicial officers from insult, but to safeguard the right to a fair trial, legal certainty, and the continuous, unhindered administration of justice as core elements of the rule of law. Such legislation should protect the integrity and authority of the courts in a way that reinforces democratic accountability and restores public confidence in the judiciary as an institution, rather than serving as a blunt instrument to silence criticism or privilege judicial dignity over systemic transparency.